Dental treatment anxiety in adults in the Canton of Saraguro, Ecuador 2021 - Sarango González, María Mercedes (2022)
Objetives: To determine the frequency of anxiety about dental treatment in the adult population of Cantón Saraguro, Ecuador. Materials and methods: A descriptive cross-secctional study.The sample consisted of a total of 403 adults from the Canton Saraguro. Data obtained through the survey called “Anxiety to dental treatment”. The same registered in the Excel.  The analysis of the information was carried out through the Chi-square stadistical test. Results: The frequency of axienty to dental treatment in the adult population of Cantón Saraguro was 78.16%. Conclusions: It was determined that the prevalence of axienty to dental treatment is relatively high, so this instrument should be implemented in the dental office to identify the degree of anxiety of the patient in different situations.